Exploring the self-reported physical fitness and self-rated health, mental health disorders, and body satisfaction among Chinese adolescents: A cross-sectional study - Shi, Chongyan; Yan, Jin; Wang, Lei; Shen, Hejun (Frontiers in Psychology, 2022)
Background Physical activity (PA) and Physical fitness (PF) have received tremendous attention in the field of physical and mental health. However, limited attention has been given to the associations of self-reported physical fitness with some health-related outcomes. Given the COVID-19 pandemic is still active in many Chinese regions, assessing health-related physical fitness (HRPF) in adolescents using field-based assessment (such as a shuttle run for cardiorespiratory fitness) is unrealistic, therefore, this study was conducted via a self-reported questionnaire. Purpose The present cross-sectional study was aimed at delving into the relationship between self-reported physical fitness with self-rated health, depression, anxiety, and body satisfaction in adolescents. Three thousand eight hundred and seven study participants from 12 public schools in South-eastern China were recruited and 2,407 of them provided valid data on variables that this study needed for analysis. Materials and methods Study participants were asked to self-report their sociodemographic factors (e.g., sex, grade, age), independence, and outcomes. Generalized linear models were used to explore the associations of self-reported physical fitness (comprising general physical fitness, cardiorespiratory fitness, muscular strength, speed and agility, and flexibility) with depression, anxiety, and body satisfaction. A total of 2,407 children and adolescents with a mean age of 13.82 (±2.1) years were included in the final study analysis. Results Higher self-reported levels of general physical fitness and cardiorespiratory fitness were associated with better self-rated health, and body satisfaction but with lower risks of depression and anxiety. Conclusion The current study offered evidence on the roles of self-reported physical fitness and health-related outcomes. To facilitate health in children and adolescents, advocating fitness education, and promotion could be a feasible approach.